Supporting Science Process Skills of Primary Students through Active Learning with Board Games - Pooripat Poohuadorn; Prasart Nuangchalerm (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
The objectives of this research aimed to compare science process skill and learning achievement of primary students between before and after instruction using active learning with board games. This research was an experimental study using a one-group pretest-posttest design. The participants were 33of grade 2 students in academic year 2025 from Mahasarakham province, Thailand. The research instruments were: 1) a lesson plan using active learning with board games on the topic of “light and living things”, and 2) and science process skill assessment test. Data analysis revealed that students who learned using active learning with board games had an average score of science process skill by post-test score higher than pre-test score at the 0.05 level of statistical significance. The scores of science process skill can be shown that the instruction supported students to deal with science lessons as well.